Effects of descending positive end-expiratory pressure on lung mechanics and aeration in healthy anaesthetized piglets - Carvalho, Alysson Roncally S (BioMed Central, 2006)
INTRODUCTION: Atelectasis and distal airway closure are common clinical entities of general anaesthesia. These two phenomena are expected to reduce the ventilation of dependent lung regions and represent major causes of arterial oxygenation impairment in anaesthetic conditions. The behaviour of the elastance of the respiratory system (E(rs)), as well as the lung aeration assessed by computed tomography (CT) scan, was evaluated during a descendent positive end-expiratory pressure (PEEP) titration. This work sought to evaluate the potential usefulness of E(rs )monitoring to set the PEEP in order to prevent tidal recruitment and hyperinflation of healthy lungs under general anaesthesia. METHODS: PEEP titration (from 16 to 0 cmH(2)O, tidal volume of 8 ml/kg) was performed, and at each PEEP, CT scans were obtained during end-expiratory and end-inspiratory pauses in six healthy, anaesthetized and paralyzed piglets. The distribution of lung aeration was determined and the tidal re-aeration was calculated as the difference between end-expiratory and end-inspiratory poorly aerated and normally aerated areas. Similarly, tidal hyperinflation was obtained as the difference between end-inspiratory and end-expiratory hyperinflated areas. E(rs )was estimated from the equation of motion of the respiratory system during all PEEP titration with the least-squares method. RESULTS: Hyperinflated areas decreased from PEEP 16 to 0 cmH(2)O (ranges decreased from 24–62% to 1–7% at end-expiratory pauses and from 44–73% to 4–17% at end-inspiratory pauses) whereas normally aerated areas increased (from 30–66% to 72–83% at end-expiratory pauses and from 19–48% to 73–77% at end-inspiratory pauses). From 16 to 8 cmH(2)O, E(rs )decreased with a corresponding reduction in tidal hyperinflation. A flat minimum of E(rs )was observed from 8 to 4 cmH(2)O. For PEEP below 4 cmH(2)O, E(rs )increased in association with a rise in tidal re-aeration and a flat maximum of the normally aerated areas. CONCLUSION: In healthy piglets under a descending PEEP protocol, the PEEP at minimum E(rs )presented a compromise between maximizing normally aerated areas and minimizing tidal re-aeration and hyperinflation. High levels of PEEP, greater than 8 cmH(2)O, reduced tidal re-aeration but increased hyperinflation with a concomitant decrease in normally aerated areas.